Determination of chemical links from methylamphetamine profiling data sets. (29th July 2019) - Montagnat, O.; Magee, C.; Slejko, J; McCaffrey, P.
ABSTRACT: A combination of drug profiling analysis, statistical filtering of selected data, database prioritization and comparative evaluation of potentially linked impurity profiles is utilized in order to positively confirm a set of chemical links from a large amount of data whilst maintaining the greatest significance to our stakeholders.